Hepatitis C virus (HCV) genotypes in 373 Italian children with HCV infection: changing distribution and correlation with clinical features and outcome. Issue 6 (11th May 2005) - Bortolotti, F; Resti, M; Marcellini, M; Giacchino, R; Verucchi, G; Nebbia, G; Zancan, L; Marazzi, M G; Barbera, C; Maccabruni, A; Zuin, G; Maggiore, G; et al.
Abstract : Background and aim: Little is known of hepatitis C virus (HCV) genotypes in HCV infected children. This retrospective, multicentre study investigated genotype distribution and correlation with clinical features and outcome in a large series of Italian children. Methods: Between 1990 and 2002, 373 HCV RNA positive children, consecutively recruited in 15 centres, were assayed for genotypes by a commercial line probe assay. Results: The following genotype distribution pattern was recorded: genotype 1b = 41%; 1a = 20%; 2 = 17%; 3 = 14.5%; 4 = 5%; other = 2.5%. The prevalence of genotypes 1b and 2 decreased significantly (p<0.001) among children born from 1990 onwards compared with older children (46% v 70%) while the rate of genotypes 3 and 4 increased significantly (from 8% to 30%). Children infected with genotype 3 had the highest alanine aminotransferase levels and the highest rate of spontaneous viraemia clearance within the first three years of life (32% v 3% in children with genotype 1; p<0.001). Of 96 children enrolled in interferon trials during the survey, 22% definitely lost HCV RNA, including 57% of those with genotypes 2 and 3. Conclusion: HCV genotypes 1 and 2 are still prevalent among infected adolescents and young adults in Italy but rates of infection with genotypes 3 and 4 are rapidly increasing among children. These changes could modify the clinical pattern of hepatitis C in forthcoming years as children infected with genotype 3 have the best chance of spontaneous viraemia clearance early in life, and respond to interferon in a high proportion of cases.